Análisis comparativo de la caries dental con la frecuencia de cepillado y visitas al odontólogo en los y las estudiantes de 18-30 años de edad, de la Universidad Nacional de Loja, periodo mayo-julio 2014. - Román Sánchez, Viviana Alexandra (2014)
Tooth decay is one of the most prevalent diseases among the population. Presenting consequences as loss of teeth prematurely, issues phonation, swallowing and aesthetics in individuals. All this for lack of timely dental care, poor oral hygiene and poor information about appropriate to maintain a good oral health care. For these reasons was conducted this investigation to inquire into the prevalence of dental caries and relate the frequency of brushing and dental visits in the students 18-30 years of age from the National University of Loja in the period May to July 2014. Structuring a medical history that was applied to each of the students performing a dental diagnosis by interviewing and obtaining the necessary data for the study. The sample was 894 students, students who meet the inclusion criteria and were the subject of study. Being a study of descriptive transversal. The results are that 79,75% of the study population has dental caries remains a high-risk group. Within the toothbrushing both men and women and in the age ranges 18-23 and 24-30 is done twice daily at a higher percentage. While dental visits a high percentage is done only once a year with 70% in both men and women in the two age groups. Given a list of dental caries as a result as these students only teeth once a day brushing and visits to the dentist mostly carry them out once a year and makes a smaller percentage three times a year which is what ideal. Keywords: dental caries, toothbrushing frequency, dental visits.